ANALISIS BERPIKIR KRITIS MATEMATIS MENGGUNAKAN MEDIA PEMBELAJARAN MATEMATIKA BERBASIS AUGMENTED REALITY UNTUK MENINGKATKAN KONSENTRASI SISWA - Nok Izatul Yazidah; Siti Napfiah; Rina Puspitasari (PedagoScript : Journal of Teaching and Texts (PJTT), 2026)
Mathematics learning is frequently perceived by students as difficult and unengaging due to the prevalence of abstract concepts that are challenging to visualize. This condition contributes to low levels of learning concentration and underdeveloped mathematical critical thinking skills among students. Mathematical critical thinking and learning concentration are essential competencies in 21st-century mathematics education; however, conventional instructional approaches often face limitations in effectively facilitating these competencies. This study aims to examine the role of Augmented Reality (AR)-based mathematics learning media in facilitating students’ mathematical critical thinking skills and enhancing their learning concentration. The study employed a descriptive qualitative research design, with fourth-grade students of MI Raden Patah as the research participants. Data were collected through classroom observations and semi-structured interviews. The findings indicate that the use of AR-based learning media enhances students’ learning focus, promotes active participation, and stimulates key indicators of mathematical critical thinking, including analyzing, evaluating, and drawing systematic conclusions. These results suggest that interactive learning media such as Augmented Reality contribute to more meaningful and engaging learning experiences and support the development of higher-order thinking skills. Therefore, Augmented Reality-based learning media represent a viable and innovative alternative for improving the quality of mathematics instruction.